Traditional Chinese decoction Si Zhi Wan attenuates ovariectomy (OVX)-induced bone loss by inhibiting osteoclastogenesis and promoting apoptosis of mature osteoclasts - He, Qingman; Fu, Kanghua; Yao, Huan; Wei, Shujun; Xiang, Li; Liu, Sixian; Chen, Tao; Gao, Yongxiang (Frontiers in Pharmacology, 2022)
Si Zhi Wan (SZW) is a traditional Chinese decoction used for osteoporosis treatment. Currently, the effect of SZW on ovariectomy (OVX)-induced bone loss and the underlying mechanisms remain unknown. Herein, we investigated the therapeutic effect of SZW on osteoporosis and explored the underlying mechanisms in vitro and in vivo. An OVX-induced bone loss model was established in vivo. After administration of SZW for eight weeks, rats were sacrificed, and the uterus was weighted to calculate its index. The femur change was pathologically evaluated using hematoxylin & eosin (H&E) staining. The mineral density of the femur was observed by micro-CT. RAW264.7 cells were activated by receptor activator of nuclear factor-κB ligand (RANKL) in vitro. The effect of SZW on osteoclastogenesis was evaluated using tartrate-resistant acid phosphatase (TRAP) staining, Western blotting, and RT-PCR. The pro-apoptosis effect of SZW on mature osteoclasts was examined after induction of osteoclast maturation. Finally, the effect of SZW on the NF-κB pathway was evaluated. Our results demonstrated that SZW ameliorated OVX-induced bone loss in rats. In addition, SZW inhibited osteoclastogenesis and attenuated osteoclast-mediated bone resorption in vitro and in vivo. SZW also promoted apoptosis of mature osteoclasts. Mechanically, SZW exerts its effects by suppressing the NF-κB pathway. Overall, these findings demonstrated that SZW may be a potentially effective alternative treatment for osteoporosis.